Differential Expression of Proteins Related to Primary Metabolism in 'Moncada' Mandarin Leaves with Contrasting Fruit Load - Munoz-Fambuena, Natalia; Mesejo, Carlos; Agustí, Manuel; Tarraga, Susana; Iglesias, Domingo J.; Primo-Millo, Eduardo; González-Mas, María C. (2017)
A proteomic study was used to know how the primary metabolism in Citrus leaves is affected by the fruit load. To this end, we researched the differential expression of proteins related to these processes between on-crop and off-crop ‘Moncada’ mandarin leaves. Samples were collected in November and proteins were extracted. From 2D DIGE gel of these extracts, 33 spots related to primary metabolism were isolated: 26 spots being associated with photosynthesis and carbohydrate metabolism, 4 spots related to Krebs cycle, 1 spot related to pentose phosphate pathway, and 2 spots related to nutrient reservoir activity. These spots were identified by MALDI-MS or LC-MS-MS. Between the proteins related to photosynthesis and carbohydrate metabolism, 16 were up-expressed in off-crop leaves, such as NADP-dependent glyceraldehyde-3-phosphate dehydrogenase, RuBisCO large subunit, ADP-glucose pyrophosphorylase, cinnamoyl-CoA reductase, and carbonic anhydrase; while 10 proteins were up-expressed in on-crop leaves such as NADP-dependent malic enzyme, and 3,4-dihydroxy-2-butanone kinase. The isolated proteins related to pentose phosphate pathway (6-phosphogluconate dehydrogenase) and to nutrient reservoir activity (Granule-bound starch synthase Ib precursor) were up-expressed in off-crop leaves. Regarding the proteins related to Krebs cycle, only malate dehydrogenase was up-expressed in off-crop leaves, while the other proteins were up-expressed in on-crop leaves (citrate synthase and NADP-isocitrate dehydrogenase). According to these results, the primary metabolism seems to be more active in off-crop leaves, suggesting that fruit load inhibits the primary metabolism in ‘Moncada’ mandarins.